Optimization of Evodiamine-Imprinted Composite Membrane by Orthogonal Design Method - Cheng1, Huiling; He1, Guangyan; Zhu1, Xiufang; Zhou1, Hao; Wang2, Mingfeng; Cao1, Qiue; Ding†, Zhongtao (Asian Journal of Chemistry, 2013)
In the study, a series of molecularly imprinted composite membranes (MICMs) for evodiamine were prepared by orthogonal experiment design involving four factors, each at three levels. The results indicated that the imprinted membrane derived from commercial cellulose acetate and nylon microfiltration membranes in tetrahydrofuran yielded the highest imprinting factor of 3.099. Characterization results by scanning electron microscopy and N2 adsorption analysis showed that the optimized imprinted membrane (MICMopt) possessed different pore structure and surface morphology from the non-imprinted membrane (NICMopt). Under the drive of concentration difference, MICMopt can preferably transfer evodiamine and its transfer mechanism conforms to the “gate effect” mechanism. As a result of imprinting effect, MICMopt can enrich evodiamine from the crude extraction of the herb Evodia rutaecarpa with a concentration effect (1.72 times). The results show a promising application potential of MICMopt in the separation and enrichment of evodiamine in the complex system.